The Working People of Paris, 1871-1914 - Berlanstein, Lenard (Johns Hopkins University Press, 2019)
Originally published in 1984. In The Working People of Paris, 1871-1914, Lenard Berlanstein examines how technological advances, expanding industrialization, bureaucratization, and urban growth affected the lives of the working poor and near poor of one of the world's most influential cities during an era of intense social and cultural change. Berlanstein departs from other historians of the working classes in treating, in a parallel manner, not only craftsmen and factory laborers but also service workers and lower-level white-collar employees. Avoiding the fallacy of letting the city limits set the boundaries of an urban study, he deals also with the industrial suburbs, with their considerable concentration of workers, to examine the transformation of the work, leisure, and consumer experiences of the people who did not own property and who lived from one payday to the next during the Second Industrial Revolution.The Working People of Paris describes a cycle of adaptation and resistance to the forces of economic maturation. For several decades after 1871, Berlanstein argues, working people and employees preserved accommodations with management about reciprocal rights in the workplace. By the beginning of the twentieth century, however, these forms of adaptation had broken down under new economic pressures. The result was a crisis of discipline in the workplace, as wage earners and modest clerks began to challenge managerial authority.Berlanstein's study confronts the widely accepted view that, during this period, workers became better integrated into a society of improving standards of living and mass leisure. Instead, he documents uneven patterns of material progress and growing conflict over work roles among all sorts of laboring people.